O desenvolvimento da disciplina da transação no direito privado brasileiro e seu papel como instrumento de autoregulação dos conflitos entre particulares - Siebeneichler De Andrade, Fábio (2023)
The work intends to examine the particularities of the settlement as a contract, based on the recognition of this legal nature, by the Civil Code of 2002. Since settlement is a legal instrument of great practical and theoretical importance, whose main purpose lies in serving to regulate conflicts between individuals, through reciprocal concessions, it is considered necessary to highlight and examine its particularities, within the framework of contracts and verify the development given to it by jurisprudence in the twenty years of validity of the 2002 Civil Code. Furthermore, it is worth highlighting the new position attributed to settlement by the new Brazilian Civil Procedure Code of 2015.